Implementation of Child-friendly School Incentive Education in Preventing Bullying Behavior among Students - Damayanti, Devi; Mashudi; Fatmawati, Erma (Universitas Veteran Bangun Nusantara, 2024)
ABSTRACT This study aims to explore the implementation of child-friendly schools as an effort to prevent bullying behavior at SD Darus Sholah Jember. The research method used is qualitative with a phenomenological approach. Data collection was done through observation, interview, and documentation. The results showed that the implementation of child-friendly schools at SD Darus Sholah Jember is manifested in various aspects, including the enforcement of discipline without violence, educational affirmation, the search for children who have not been reached by education, commitment to freedom from narcotics, psychotropic substances, and addictive substances, school security from disasters, guaranteeing the protection of students' rights to worship according to their respective religions, and implementing a child-friendly curriculum. The findings confirm the important role of schools as safe, inclusive and supportive environments for children's development. The implications of this study can be used as a basis for developing more effective educational policies and practices in preventing bullying behavior and creating a conducive learning environment for all students. Further research can be in-depth on the factors that influence the successful implementation of child-friendly schools and the evaluation of their impact on students' well-being. Keywords: Child- Friendly School, Incentive education, Preventing bullying